HIV update: Where are we now?. Issue 5 (September 2018) - Shannon, Mary
Abstract : Although there have been many advances in the past 30 years, HIV remains a healthcare concern throughout the world. Nurses play a critical role in educating patients about HIV transmission, treatment, and prevention, as well as identifying at-risk patients for preexposure prophylaxis. Abstract : Although there have been many advances in the past 30 years, HIV remains a healthcare concern throughout the world. Nurses play a critical role in educating patients about HIV transmission, treatment, and prevention, as well as identifying at-risk patients for preexposure prophylaxis.